Identification of RMP24 and RMP64, human ribonuclease MRP-specific protein components - Rui Che; Bhoomi Mirani; Monireh Panah; Xiaotong Chen; Hong Luo; Andrei Alexandrov (Cell Reports)
Summary: Human RNase MRP is a ribonucleoprotein (RNP) enzyme that processes precursor rRNA (pre-rRNA) at ITS1 site 2 and may have additional activities. It is an endonuclease related to RNase P, which processes pre-tRNAs and pre-tRNA-like substrates. In Saccharomyces cerevisiae, these two RNPs utilize distinct catalytic RNAs with eight shared and one or two specific protein subunits. However, the human RNase MRP-specific protein subunits remain unidentified. Our genome-wide forward genetic screening identifies two poorly characterized human genes, which we name ribonuclease MRP subunit P24 (RMP24) and RMP64. We show that Rmp24 and Rmp64 are required for pre-rRNA ITS1 site 2 processing and associate with MRP RNA but are not required for RNase P activity and do not associate with RNase P-specific H1 RNA. Despite limited sequence homology, Rmp24 and Rmp64 exhibit predicted structural similarities to two RNase MRP-specific components in S. cerevisiae. Collectively, our functional screening and validation reveal two protein components unique to human nuclear RNase MRP.